EVALUASI KETERSEDIAAN KOLEKSI LITERATUR BUKU KEISLAMAN DI PERPUSTAKAAN MADRASAH IBTIDA’IYAH NAHDLATUL ULAMA’ SUMPUT TAHUN AJARAN 2022/2023 - M. Athoiful Fanan; Anya Olimvia Wimpi Suwandi Putri; Siti Mashito Novita (STAI AN-NAJAH INDONESIA MANDIRI, 2022)
Evaluate the availability of library collections to measure the availability of Islamic book literature collections in libraries using certain steps. Summarizing this is an evaluation of the availability of literature collections that have been achieved or have not been achieved. The research method is a qualitative method, namely by taking data by observation, interviews and documentation to be connected to existing topics and theories. The results of the study illustrate that the schedule of library activities and also the collection of Islamic book availability in the library of Madrasah Ibtida'iyah Nahdlatul Ulama' Sumput yamg where the average Islamic book in the library of Madrasah Ibtida'iyah Nahdlatul Ulama' Sumput is only about 40% of other books. There are also a number of other Islamic books. There is also a list of student visits in the library of Madrasah Ibtida'iyah Nahdlatul Ulama' Sumput. Students are also allowed to borrow books with a period of 2 days. If it exceeds this time period, it will be subject to fines and if there are missing books then the student is required to replace. With this, the availability of books in the library of Madrasah Ibtida'iyah Nahdlatul Ulama' Sumput is still incomplete. And also evaluate the availability of this Islamic book collection still needs improvement. Keywords: evaluation, Islamic books, library. References Rati Novita Ningsih, ‘Evaluasi Ketersediaan Koleksi Di Perpustakaan SMA Negeri 5 Yogyakarta (Bersadarkan Kajian Terhadap Silabus Kurikulum KTSP Mata Pelajaran Muatan Lokal)’, 2009, i-xxi;1-15;81-84 Lailah Talbiah, ‘Evaluasi Ketersediaan Koleksi Buku Pelajaran Dalam Memenuhi Kebutuhan Informasi Siswa di Perpustakaan SMA Negeri 8 Bulukumba’, Ilmu Perpustakaan, 2008 Farih Faruk Musafir,’Evaluasi Pemanfaatan dan Ketersediaan Koleksi Perpustakaan FAH UIN Syarif Hidayatullah Berdasarkan Analisis Sitiran Artikel Karya Ilmiah Pada Jurnal Al-Turas’,Ilmu Perpustakaan, 2017-2019. Iztihana, Affa, and Mecca Arfa, ‘Peran Pustakawan MTs N 1 Jepara Dalam Upaya Mengembangkan Minat Kunjungan Siswa Pada Perpustakaan’, Ilmu Perpustakaan, 9.1 (2020), 93–103 Saleh, Sirajuddin, S Pd, M Pd, Dkk Helaluddin, Jozef Raco, and others, ‘Metodologi Penelitian Kualitatif.Pdf’, 2019, pp. 11–11 analiya dewi, ‘Kabupaten Pekalongan’, Pekalongankab.Go.Id, 5.6 (2019), 1–65 Ulpiatiah Umar,’Hubungan Jam Buka Pelayanan Perpustakaan Dengan Minat Kunjungan Pemustaka di Perpustakaan SMA Guppi Samata Gowa’,2017. Aziz Alfarisy, Yanuar Yoga Prasetyawan,’Dampak Program Jadwal Kunjungan Perpustakaan Terhadap kemampuan Literasi Informasi Siswa di Gandhi Memorial International School Semarang’, Ilmu Perpustakaan, Ilmu Budaya 2015. Junaeti,’Ketersediaan Koleksi Berdasarkan Silabus dan Standar BAN-PT: Analisis Koleksi Perpustakaan IAIN Pekalongan Untuk Jurusan Pendidikan Agama Islam FTIK IAIN Pekalongan’,June 2019. Mutmainnah,’Evaluasi Keterpakaian Koleksi Buku Pelajaran Agama Islam Dalam Kegiatan Belajar Mengajar di SMA Muhammadiyah Kalosi Kabupaten Enrekang’,2016.